1995
DOI: 10.1080/00029157.1995.10403160
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Hypnosis in Helping Cancer Patients Control Anxiety, Pain, and Emesis: A Review of Recent Empirical Studies

Abstract: This is a review of the systematic studies conducted since 1980 in the area of hypnotic interventions for anxiety, pain, and emesis control in child and adolescent cancer patients. The focus of the present paper is on how the problems encountered in studying the use of hypnosis with this population influence the results. The review is divided between studies focused on controlling anxiety and pain and those focused on controlling nausea and vomiting. Consistent findings are identified, and suggestions for futu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(20 citation statements)
references
References 13 publications
0
19
0
1
Order By: Relevance
“…One review found that hypnosis significantly reduces anxiety and pain experienced by patients with cancer [100]. Another review determined that there is moderate evidence to support the use of hypnosis for the treatment of acute and chronic pain conditions.…”
Section: Mind-body Medicinementioning
confidence: 95%
“…One review found that hypnosis significantly reduces anxiety and pain experienced by patients with cancer [100]. Another review determined that there is moderate evidence to support the use of hypnosis for the treatment of acute and chronic pain conditions.…”
Section: Mind-body Medicinementioning
confidence: 95%
“…85 Studies have demonstrated that hypnosis can be an effective means for some cancer patients to alleviate nausea and vomiting associated with chemotherapy. 86 Hypnotic effects are thought to occur through 3 primary mechanisms, muscle relaxation, perceptual alteration, and cognitive distraction. 87 Hence.…”
Section: Hypnosismentioning
confidence: 99%
“…Il va de soi que, sur un plan pratique, les études de survie impliquent un suivi plus long des patients et les résultats ne se montrent que beaucoup plus tardivement, contrairement aux impacts sur l'humeur ou la qualité de vie qui peuvent se mesurer à chaque étape de la prise en charge. D'autres études ont porté sur une diminution des effets secondaires pendant les traitements (nausées, vomissements…) et aussi sur la douleur, entre autres grâce à l'hypnose (Wall, 1989 ;Jacknow, 1994 ;Genuis, 1995) avec des résultats favorables.…”
Section: Objectif Des Recherchesunclassified